Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/978-3-319-05401-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Structure Comparison of Binary and Weighted Niche-Overlap Graphs

Abstract: Abstract. In ecological networks, niche-overlap graphs are considered as complex systems. They represent the competition between two predators that share common resources. The purpose of this paper is to investigate the structural properties of these graphs considered as weighted networks and compare their measures with the ones calculated for the binary networks. To conduct this study, we select four classical network measures : the degree of nodes, the clustering coefficient, the assortativity, and the betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This indicates that species in these networks tend to be randomly linked, which goes in the same direction of a previous study where these networks were found to follow a single scale degree distribution [17].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates that species in these networks tend to be randomly linked, which goes in the same direction of a previous study where these networks were found to follow a single scale degree distribution [17].…”
Section: Resultssupporting
confidence: 82%
“…Two species are linked if they share at least one prey. In this paper, we extended the work introduced in [17] where it was shown that a collection of 15 niche-overlap graphs do not exhibit « small world » nor « scale-free » properties. We moreover compared their structure with random niche-overlap graphs to acquire a better comprehension of these patterns.…”
Section: Introductionmentioning
confidence: 87%